2006
DOI: 10.1007/s11527-005-9045-0
|View full text |Cite
|
Sign up to set email alerts
|

Time dependent behavior of elements combining ultra-high performance fiber reinforced concretes (UHPFRC) and reinforced concrete

Abstract: Structural elements combining Ultra-High Performance Fiber Reinforced Concretes (UHPFRC) and concrete offer a high potential in view of rehabilitation and modification of existing structures. The investigation of the time-dependent behavior of composite "UHPFRC-concrete" elements is a fundamental step in the determination of durability and serviceability. For this, an experimental program was conducted on large composite "UHPFRC-concrete" beams and a numerical model was validated with the test results. The exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
1
6

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 8 publications
2
65
1
6
Order By: Relevance
“…Thus, the stress carrying capacity of UHPFRC under tensile fatigue significantly decreases when the material deformation is within the equivalent strain-hardening domain. Habel [15] reported similar findings from cyclic tensile tests on a different UHPFRC mix (CEMTEC multiscale Ó).…”
Section: (2) Variations In Local Deformationsupporting
confidence: 52%
“…Thus, the stress carrying capacity of UHPFRC under tensile fatigue significantly decreases when the material deformation is within the equivalent strain-hardening domain. Habel [15] reported similar findings from cyclic tensile tests on a different UHPFRC mix (CEMTEC multiscale Ó).…”
Section: (2) Variations In Local Deformationsupporting
confidence: 52%
“…Generally, the reported setting time of UHPC ranged from 6 to 12 h depending on the mixture design (Richard and Cheyrezy 1995;Yoo et al 2013;Kazemi and Lubell 2012). However, some studies (Brown 2006;Graybeal 2007;Habel 2004;Morin et al 2001) showed that the setting time for UHPC can be delayed for up to 30-40 h due to the set retarding effect of high SP dosage. Furthermore, it was observed that surface covering of freshly mixed UHPC delayed its setting time (Yoo et al 2013).…”
Section: Setting Timementioning
confidence: 99%
“…Mould M3 was used for a test in a thin layer of special repairing mortar made of high performance fibre-reinforced cement-based material (UHPFRC) [29]. The testing of this material posed particular challenges.…”
Section: Specimen and Sensor Characteristicsmentioning
confidence: 99%